Structural and electronic properties of hydrogenated GaBi and InBi honeycomb monolayers with point defects. Issue 13 (13th February 2018) - Zhang, Yunzhen; Ye, Han; Yu, Zhongyuan; Gao, Han; Liu, Yumin
Abstract : Vacancies, antisites and Stone–Wales defects in H2 -Ga(In)Bi monolayer are investigated using first-principles calculations. Abstract : First-principles calculations are carried out to systematically investigate the structural and electronic properties of point defects in hydrogenated GaBi and InBi monolayers, including vacancies, antisites and Stone–Wales (SW) defects. Our results imply that the perfect H2 -Ga(In)Bi is a semiconductor with a bandgap of 0.241 eV (0.265 eV) at the Γ point. The system turns into a metal by introducing a Ga(In) vacancy, substituting a Bi with a Ga(In) atom or substituting an In with a Bi atom. Other defect configurations can tune the bandgap value in the range from 0.09 eV to 0.3 eV. In particular, the exchange of neighboring Ga(In) and Bi increases the bandgap, meanwhile the spin splitting effect is preserved. All SW defects decrease the bandgap. The lowest formation energy of defects occurs when substituting a Ga(In) with a Bi atom and the values of SW defects vary from 0.98 eV to 1.77 eV.